Genetics for the Women's Health Trainee: A Five-Module Curriculum - Sarah K. Dotters-Katz; Neeta Vora; Jeffrey Kuller (Association of American Medical Colleges, 2019)
Introduction Genetics is ubiquitous in OB-GYN. However, data suggest that trainees feel underprepared to counsel patients about genetic testing, the nuances of which are becoming increasingly complicated. We sought to develop and implement a genetics curriculum for OB-GYN residents. Methods This five-module (screening for fetal aneuploidy, prenatal diagnostic testing, prenatal carrier screening, pedigrees, and cancer genetics), interactive, case-based curriculum is linked to Council on Resident Education in Obstetrics and Gynecology objectives and can stand alone or work as part of an ultrasound or obstetrics rotation. Each module, containing objectives, assigned readings, and cases with answers, is used in a small-group format and can be completed in 20-30 minutes prior to the start of a clinical day. Modules were implemented at two academic centers with first-year OB-GYN residents. Qualitative real-time feedback and summative quantitative feedback from OB-GYN residents were obtained. Results Twenty-one OB-GYN residents completed the curriculum, which was well received by trainees and program directors. All residents (100%) felt the curriculum increased knowledge of prenatal genetics and felt more comfortable counseling patients after completion. Seventy-three percent enjoyed the discussion/case-based format; associated articles were found helpful by 100% of trainees. Facilitators enjoyed teaching the curriculum and felt learner knowledge improved dramatically. Discussion These low-cost modules were easy to implement and resulted in increased knowledge and confidence in prenatal and cancer genetics. Designed to stand alone and take as little as 20 minutes, the modules provide a helpful adjunct to a women's health rotation or didactic curriculum.